Hasil Pengabdian Masyarakat Latihan dan Perkenalan Bela Diri Praktis Di Sekotong Barat - Adi suriatno; Rusdiana Yusuf; Likman; Tiassari Janjang Suminar; Kokom Supryatnak (Jurnal Pengabdian kepada Masyarakat Cahaya Mandalika (Abdimandalika), 2025)
Security and physical resilience are important aspects in everyday life that can increase feelings of security and self-confidence in facing various situations. The community service program entitled "Training and Introduction to Practical Self-Defense in West Sekotong" aims to introduce practical self-defense techniques that can be accessed by all groups, especially teenagers and women, to increase feelings of security and confidence in daily activities. Martial arts, apart from teaching physical defense techniques, also plays a role in mental development, discipline and awareness of the importance of physical health. This program is based on research showing that self-defense training can increase mental resilience and provide participants with a sense of security. Training activities were carried out for four weeks, with two sessions per week, consisting of an introduction to the basics of self-defense, physical training to increase strength and agility, as well as simulations of real situations to train quick responses in emergency conditions. Apart from that, this program also includes providing motivation and mental training to strengthen participants' mental toughness. Through this training, it is hoped that participants can master basic self-defense skills that can be applied in everyday life and increase self-confidence and mental resilience in facing life's challenges.